2004
DOI: 10.1111/j.1747-7379.2004.tb00189.x
|View full text |Cite
|
Sign up to set email alerts
|

International Migrants’ Remittances and Welfare Status of the Left-Behind Families in Turkey

Abstract: In this study, micro implications of remittances are examined based on the data from the 1996 Turkish International Migration Survey (TIMS‐96), part of a comprehensive study of Eurostat and the Netherlands Interdisciplinary Demographic Institute (NIDI). Results of the study imply that migrant savings are generally used for satisfying basic consumption needs. Patterns of expenditures suggest that for 12 percent of all the households receiving remittances, about 80 percent used remittances to improve their stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(57 citation statements)
references
References 8 publications
6
51
0
Order By: Relevance
“…For example, Itzigsohn (1995) found that in Dominican Republic remittances constitute nearly 40% of the total income of households with labor migrants and in Jamaica, remittances constitute about third of total household income. Moreover, the economic standing (measured by total income and by standard of living) of households that receive remittances is higher than the economic standing of households without labor migrants (Koc and Onan 2004;Itzigsohn 1995). Indeed, households in labor-sending societies use remittances for improvement of standard of living and for economic mobility (Itzigsohn 1995;Zlotnik 1990;Eelens and Speckmann 1990).…”
Section: The Role Of Remittances: General Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Itzigsohn (1995) found that in Dominican Republic remittances constitute nearly 40% of the total income of households with labor migrants and in Jamaica, remittances constitute about third of total household income. Moreover, the economic standing (measured by total income and by standard of living) of households that receive remittances is higher than the economic standing of households without labor migrants (Koc and Onan 2004;Itzigsohn 1995). Indeed, households in labor-sending societies use remittances for improvement of standard of living and for economic mobility (Itzigsohn 1995;Zlotnik 1990;Eelens and Speckmann 1990).…”
Section: The Role Of Remittances: General Discussionmentioning
confidence: 99%
“…Substantial portions of their earnings are remitted to family members left behind (Semyonov and Gorodzeisky 2005). The remittances are often used to combat poverty and to overcome economic hardships in place of origin and help family members to raise standard of living and to improve quality of life (Koc and Onan 2004;Itzigsohn 1995;Findley 1994;Eelens and Speckmann 1990;Zlotnik 1990). From this point of view, labor migration is viewed, indeed, as a rational economic survival strategy of some poor but mostly lower middleincome households in less developed countries (e.g.…”
mentioning
confidence: 98%
“…This is in contrast to the literature that, barring a few exceptions (Calero, Bedi, and Sparrow 2009;Cortes 2011), has by and large treated educational expenditure as a form of consumption rather than as a "productive investment" since it does not result in the immediate employment of resources (Koc and Onan 2004). Our proxy for educational investments is the expenditure share on schooling.…”
Section: Discussionmentioning
confidence: 93%
“…Unskilled, domestic work provides few opportunities for human capital accumulation and transfer of knowledge that women can utilize following their return home. Lack of financial literacy and social capital, limited opportunities for business investments, and cultural and institutional barriers also constrain the ability of female return migrants to invest remittances productively in selfemployment and asset markets (Koc and Onan 2004). In households that are left behind, the absence of the primary caregiver may inhibit the wellbeing and long-term health and education prospects of the children (Cortes 2011;McKenzie and Rapoport 2011) and intra-household bargaining problems may divert migrant earnings toward uses preferred by other household members (Guzman, Morrison, and Sjöblom 2008;Ashraf et al 2011;Chin, Karkoviata, and Wilcox 2011).…”
Section: Introductionmentioning
confidence: 99%
“…During the period 1950s and 1960s, optimistic (developmentalist and neoclassical) school of thought argues that remittances have positive effects on poverty reduction of the receiving areas. This school of thought focus that remittance is the important factor for increasing living standards and economic condition of the poor without considering whether the remittances are used for consumption, buying house or other investment (Zachariah et al, 2001;Koc, 2004;Adams, 2005;World Bank, 2007, Acosta et al, 2007. Contrary to the optimistic views, the pessimistic school of thought argued that remittances have negative effect on poverty.…”
Section: Theoretical Bases Of the Studymentioning
confidence: 99%